Mulberry (Morus alba L.) leaf extract enhanced spermatozoa motility, viability, and plasma membrane integrity of rats (Rattus norvegicus) exposed to e-cigarette smoke - Ramadhani, Fifi Fauziah; Yulianna Puspitasari; Hermin Ratnani; Budi Utomo; Rochmah Kurnijasanti; Kadek Rachmawati (Ovozoa: Journal of Animal Reproduction, 2024)
This study investigates the impact of mulberry leaf extract on the viability, plasma membrane integrity, and motility of spermatozoa from male white rats (Rattus norvegicus) exposed to e-cigarette smoke. A total of twenty-five male rats were divided into five groups: negative control (NC), positive control (PC), T1, T2, and T3. All groups, except for the NC group, were exposed to e-cigarette smoke. Rats in the T1, T2, and T3 groups received mulberry leaf extract in doses of 100, 200, and 400 mg/kg bw, respectively, while the NC and PC groups were given a placebo of 1% Na-CMC. Both the mulberry leaf extract and the placebo were administered daily, beginning three days prior to the start of e-cigarette smoke exposure, which lasted for 28 days. Results showed that spermatozoa motility, plasma membrane integrity, and viability in the experimental groups were significantly lower than those in the NC group (p <0.05). Conversely, rats in the T1, T2, and T3 groups that received mulberry leaf extract demonstrated significantly greater spermatozoa viability, plasma membrane integrity, and motility compared to the PC group (p <0.05). The T3 group exhibited the most pronounced improvements, with significantly enhanced spermatozoa viability, membrane integrity, and motility (p <0.05) relative to the PC group. These results indicate that mulberry (Morus alba L.) leaf extract enhanced spermatozoa viability, plasma membrane integrity, and motility in white rats (Rattus norvegicus) subjected to e-cigarette smoke.